Actellic 2% Dust as Pesticide in Feed Ingredients: Post-Weaning Tolerance, Growth Performance and Organ Weights of Growing Rabbits - Omoyakhi, J.M.; Orheruata, A.M. (Pakistan Journal of Nutrition, 2009)
The study was designed to evaluate the tolerance, survivability and performance of weaner rabbits fed varying levels of actellic dust. The pathological effects of the pesticide on the animals were also appraised. A uniform diet was compounded from ingredients certified to be apparently pesticide residue-free. This diet was partitioned into 5 sub-diets. The first partition A had no residue, serving as control while B, C, D and E had 0.01, 0.02, 0.03 and 0.04% inclusion of the actellic dust, respectively. A total of 20 rabbits of mixed breeds and sexes were used in the experiment. The animals were balanced for breed, sex and weight in a completely randomized design experiment. Four animals each were placed on each treatment diets for 45 days which were preceded by 3 weeks of acclimatization. Data on feed intake and weight gain were collected on weekly basis. Data on blood volume and organ weight were also obtained at the end of the study. Feed intake reduced with progressive inclusion of actellic dust. The average daily feed intakes were 71.40g (A), 66.04g (B) 64.82g (C), 67.56g (D) and 63.79g (E) though not significantly different (P > 0.05) Weight gain however increased with increase dosage of the animals with treatment E having the highest gain and significantly higher (p < 0.05) than treatment B but not higher (p > 0.05) than the control. Feed utilisation (feed efficiency ratio) was comparable in all treatments. Organ weights and blood volume (average values of 4.67-7.01% of body weight) were comparable among groups except for heart, spleen and liver that were significantly different (P < 0.05) indicating incidence of gross pathological changes in the group with the highest dose of actellic dust inclusion. Percentage mortality of 25 was also recorded from treatment with the highest dose. The results therefore show that weaner rabbits can tolerate the presence of actellic dust in feed up to 0.03%. At this dose, the acttellic dust does not have adverse effects on growth performance. Higher concentration of 0.04% can result in manifestation of toxicity symptoms and sometimes death, such values are rarely naturally present in feeds. However, animals which are able to tolerate high values hardly manifest poor performances.